Nutritional management and maize variety combination effectively control Striga asiatica in southern Africa - Mutsvanga, Simbarashe; Gasura, Edmore; Setimela, Peter S.; Nyakurwa, Cacious S.; Mabasa, Stanford (BioMed Central, 2022)
Maize (Zea mays L.) is an important staple food crop in sub-Saharan Africa (SSA) and contributes significantly to food security. Due to Striga, maize yield loss is estimated between 20 and 80% forcing some farmers to abandon their land therefore threatening food security. Many strategies have been applied to combat Striga infested fields to improve maize yields but alternative feasible approaches are still required. This study aimed at determining effects of phosphorus (P) and maize variety on Striga asiatica germination and attachment. A factorial experiment of eight P levels (0, 10, 20, 30, 40, 50, 60 and 70 kg ha−1), six maize varieties and Striga (inoculated and non-inoculated) in a 4 × 24 α-lattice design with three replications was set in a glasshouse at the University of Zimbabwe. A similar experiment was set under laboratory conditions using agar gel plates to determine S. asiatica germination using a complete randomized design with three replications. Adding P (at 40 kg ha−1) to soil infected with Striga, significantly (p < 0.05) reduced Striga counts and haustorial root attachments in all varieties with CV4 and R201 supporting lowest numbers. P also significantly (p < 0.05) improved plant height, chlorophyll content, leaf, cob, total biomasses and grain yield across all maize genotypes. Cultivar CV4 produced the highest grain yield under Striga attack. Furthermore, cultivars CV4 and CV1 had significantly (p < 0.05) lowest Striga seed maximum germination distance and percentages at zero P. Application of P reduced Striga germination, attachments and emergence in all varieties and increased tolerance of maize varieties.